Sceptics and a Religious Instinct (Minerva, 2019)
This article analyses the position of the sceptic thought about the religion and the belief in gods, and it concludes, although it seems the opposite, that the scepticism isn´t atheistic but it defends the acceptance of the belief in gods justified by customs and needs of worship and sacrifices to the gods for the city, without reducing the rational dimensio of man.
Keywords: Scepticism; Greek philosophy; Greek religion; Pyrrho; Timo Phliasius; theism; atheism